Alpha-Tocopherol Supplementation in Healthy Individuals Reduces Low-Density Lipoprotein Oxidation but Not Atherosclerosis: The Vitamin E Atherosclerosis Prevention Study (VEAPS) - Hodis, Howard N.; Mack, Wendy J.; LaBree, Laurie; Mahrer, Peter R.; Sevanian, Alex; Liu, Chao-ran; Liu, Ci-hua; Hwang, Juliana; Selzer, Robert H.; Azen, Stanley P. (Circulation (New York, N.Y.), 2002)
Background— Epidemiological studies have demonstrated an inverse relationship between vitamin E intake and cardiovascular disease (CVD) risk. In contrast, randomized controlled trials have reported conflicting results as to whether vitamin E supplementation reduces atherosclerosis progression and CVD events. Methods and Results— The study population consisted of men and women ≥40 years old with an LDL cholesterol level ≥3.37 mmol/L (130 mg/dL) and no clinical signs or symptoms of CVD. Eligible participants were randomized to DL-α-tocopherol 400 IU per day or placebo and followed every 3 months for an average of 3 years. The primary trial end point was the rate of change in the common carotid artery far-wall intima-media thickness (IMT) assessed by computer image-processed B-mode ultrasonograms. A mixed effects model using all determinations of IMT was used to test the hypothesis of treatment differences in IMT change rates. Compared with placebo, α-tocopherol supplementation significantly raised plasma vitamin E levels ( P <0.0001), reduced circulating oxidized LDL ( P =0.03), and reduced LDL oxidative susceptibility ( P <0.01). However, vitamin E supplementation did not reduce the progression of IMT over a 3-year period compared with subjects randomized to placebo. Conclusions— The results are consistent with previous randomized controlled trials and extend the null results of vitamin E supplementation to the progression of IMT in healthy men and women at low risk for CVD.